Analisis Komunikasi antara Penjual dan Pembeli Menggunakan Fitur Direct Message pada Media Sosial Instagram: Studi pada Akun Instagram @seafood_brother_lpg - Desma Silvira; M. Denu Poyo; Budhi Waskito (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the interpersonal communication process between sellers and buyers through the Direct Message (DM) feature on the Instagram account @seafood_brother_lpg and to understand the symbolic meanings created within the interaction. This research applied a descriptive qualitative method by collecting data through interviews, observation, and documentation.The results show that interpersonal communication through DM occurs in a two-way, interactive, responsive, and personal manner. The communication process takes place in several stages: opening, exchanging information, negotiation, and closing messages. It uses casual language, friendly greetings, emoticons, and Voice Notes, which not only facilitate transactions but also build emotional closeness and customer loyalty.Symbolic meanings are reflected through emoticons, Voice Notes, and warm greetings, representing familiarity, attention, and emotional closeness between the seller and customer. The Direct Message feature has proven effective in simplifying the ordering process, delivering information, handling complaints, and maintaining good relationships in online business.